Bioremediation Of Benzene And Its Derivatives Producing Renewable Energy Through Benthic Microbial Fuel Cells - Umar, Mohammad Faisal (2022)
Anthropogenic activities are largely responsible for the vast amounts of pollutants such as polycyclic aromatic hydrocarbons, cyanides, phenols, metal derivatives, sulphides, and other chemicals in wastewater through the source petrochemical and chemical industries. The excess benzene, toluene and xylene (BTX) can cause severe toxicity to living organisms in wastewater. Severral methods have been utilized like filtration, sedimentation, ozonation etc. BMFC is an emerging technology for the simultaneous production of renewable energy and bioremediation of BTX from wastewater by using sugar cane substrate. It is a different from microbial fuel cells because they lack a membrane. Benzene and toluene were oxidized into intermediate benzoic acid, while xylene was converted into 2-methyl benzoic acid then completely converted into carbon dioxide. The maximum potential was calculated using a multimetre, while current density and power density through the polarization curve of BMFC. UV–visible spectroscopy and cyclic voltammetry were used to determine bioremediation efficiency and specific capacitance, respectively. Electrochemical impedance spectroscopy determined the overall internal resistance, and microbiological analysis revealed the bacteria present.